Non-contiguous finished genome sequence of plant-growth promoting Serratia proteamaculans S4. Issue 3 (May 2013) - Neupane, Saraswoti; Goodwin, Lynne; Högberg, Nils; Kyrpides, Nikos; Alström, Sadhna; Bruce, David; Quintana, Beverly; Munk, Christine; Daligault, Hajnalka; Teshima, Hazuki; Davenport, Karen; Reitenga, Krista; et al.
Abstract Serratia proteamaculans S4 (previouslySerratia sp. S4), isolated from the rhizosphere of wildEquisetum sp., has the ability to stimulate plant growth and to suppress the growth of several soil-borne fungal pathogens of economically important crops. Here we present the non-contiguous, finished genome sequence ofS. proteamaculans S4, which consists of a 5, 324, 944 bp circular chromosome and a 129, 797 bp circular plasmid. The chromosome contains 5, 008 predicted genes while the plasmid comprises 134 predicted genes. In total, 4, 993 genes are assigned as protein-coding genes. The genome consists of 22 rRNA genes, 82 tRNA genes and 58 pseudogenes. This genome is a part of the project "Genomics of four rapeseed plant growth-promoting bacteria with antagonistic effect on plant pathogens" awarded through the 2010 DOE-JGI's Community Sequencing Program.